CAREER TREE PROJECT-BASED LEARNING IN THE CAREER PLANNING OF STUDENTS AT DARULRAHMAH SCHOOL, NARATHIWAT, THAILAND - Ana Ayuning Tyas; Abdi Fauji Hadiono (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2026)
Students at Darulrahmah School in Narathiwat, Thailand faced challenges in career planning, a situation largely caused by frequent absenteeism and boredom with conventional classroom learning. This study aims to examine the implementation of the Career Tree project-based learning model and to explore the perspectives of the school principal and teachers regarding its role in students’ career planning. The research employs a qualitative, descriptive field research approach, with data collected through observation, interviews, and documentation. The results reveal that the implementation of the Career Tree project-based learning at Darulrahmah School has had a significant positive impact on students’ career planning. This affirms that the learning approach is effective in preparing students to face real-world employment challenges with greater readiness and confidence